2021
DOI: 10.1007/s10799-021-00324-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organizational inertia on organizational agility: the role of IT ambidexterity

Abstract: Firms have increasingly relied on information technology (IT) to remain agile in today's hypercompetitive business environment. Drawing on the organizational inertia theory and literature on IT-enabled agile, this study examines the relationship between organizational inertia, IT ambidexterity (i.e., IT exploration and exploitation), and organizational agility. Quantitative data were collected from 326 respondents through a questionnaire survey in China and analyzed using the partial least squares structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
2
40
0
1
Order By: Relevance
“…The support of new processes built through exploration coincides with organizations' entrepreneurial orientation. In fact, due to organizational inertia, exploration is strongly resisted in organizations with deep-rooted experience [62]. A company with strong capabilities in its current field may rationally reduce its exploratory behavior due to complacency, incompatible technological paths, and cost considerations [63,64].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The support of new processes built through exploration coincides with organizations' entrepreneurial orientation. In fact, due to organizational inertia, exploration is strongly resisted in organizations with deep-rooted experience [62]. A company with strong capabilities in its current field may rationally reduce its exploratory behavior due to complacency, incompatible technological paths, and cost considerations [63,64].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, consistency in the organization’s functions and forms keeps the change process moving forward or expanding (Stieglitz et al, 2016 ). Organizational inertia is a barrier to business growth and change that can positively influence an organization’s expansion (Gilbert, 2005 ; Zhen et al, 2021 ). Inertia in the organization, for example, prevents it from implementing the processes, techniques, and procedures in place (Wang et al, 2015 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to OIT theory, an organization’s internal inertia might impede it from responding to changes in the external environment on time and engaging in reforms (Gilbert, 2005 ). The stance of inertia provides a stable sense of stable environmental situations (Zhen et al, 2021 ). When organizational capacities become more rigid, most successful businesses can collapse.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Besson and Rowe [35] define inertia as the degree of stickiness during an organizational transformation. More recent organizational inertia studies have shown that the introduction of digital technologies can also result in stickiness [36,37]. Our use of the term stickiness is closely related to the concept of organizational inertia in digital transformations, which refers to inertial forces that oppose change.…”
Section: A Practice Perspective Of Digital Hrmmentioning
confidence: 99%